Pineapple enzyme: Beneficial poultry supplement - Atirah Fatini, Zin Azmi; Shalyda, Md Shaarani @ Md Nawi; Jun Haslinda, Shariffuddin; Nasratun, Masngut; Zatul Iffah, Mohd Arshad (2021)
Pineapple waste have been reported to contain nutrients such as dietary fibres, sugars, proteins and minerals. These nurients could serve as a prominent source of growth factors to poultry. Hence, it can helps as an alternative to reduce poultry farmer’s costs to buy poultry feed.